2013
DOI: 10.1364/ol.38.004281
|View full text |Cite
|
Sign up to set email alerts
|

Frequency comb generation by a continuous-wave-pumped optical parametric oscillator based on cascading quadratic nonlinearities

Abstract: We report optical frequency comb generation by a continuous-wave pumped optical parametric oscillator (OPO) without any active modulation. The OPO is configured as singly resonant with an additional nonlinear crystal (periodically poled MgO:LiNbO3) placed inside the OPO for phase mismatched second harmonic generation (SHG) of the resonating signal beam. The phase mismatched SHG causes cascading χ(2) nonlinearities, which can substantially increase the effective χ(3) nonlinearity in MgO:LiNbO3, leading to spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 23 publications
0
71
0
Order By: Relevance
“…Operation of a Kerr comb in a pulsed regime with controlled formation of temporal solitons was recently demonstrated [9]. In contrast to these results achieved in a medium exhibiting a third-order non-linearity (Kerr effect), comb generation was also recently demonstrated by parametric processes with a second-order χ (2) non-linearity, with the potential for a lower pump threshold [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Operation of a Kerr comb in a pulsed regime with controlled formation of temporal solitons was recently demonstrated [9]. In contrast to these results achieved in a medium exhibiting a third-order non-linearity (Kerr effect), comb generation was also recently demonstrated by parametric processes with a second-order χ (2) non-linearity, with the potential for a lower pump threshold [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, four-wave mixing has also been proposed as one of the mechanisms that lead to combs generation in quantum cascade lasers [6][7][8][9]. More recently, however, OFCs have also been demonstrated in continuously driven cavities with quadratic χ (2) nonlinearity [10][11][12][13]. In particular, OFCs can be generated in a cavity with a χ (2) nonlinear crystal that is phasematched for second harmonic generation (SHG) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Although all microresonator frequency comb studies to date have revolved around third-order Kerr nonlinear effects, recent studies in macroscopic, free-space cavities have shown that similar phenomenologies can also manifest themselves in quadratically nonlinear cavities [13], [14]. In particular, experiments have shown that, similarly as for Kerr cavities, a cw laser coupled into a quadratically nonlinear cavity can transform into a frequency comb [14].…”
Section: Introductionmentioning
confidence: 99%